2008
DOI: 10.1111/j.1365-2184.2008.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously immortalized mouse mesothelial cells display characteristics of malignant transformation

Abstract: These findings have implications for interpretation of in vitro transformation studies, demonstrating broad similarity between spontaneous and induced genetic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The most used immortalized human mesothelial cell lines are MeT-5A immortalized with SV40 (Ke et al 1989 ) and LP9 cells immortalized with TERT1, the catalytic component of telomerase (Connell and Rheinwald 1983 ). Immortalized mesothelioma and mesothelial cells of mouse origin include cells isolated from the ascites of asbestos-exposed wild-type C57Bl/6J or BALB/c mice [40, 40L, AE17, AK7 (Cordier Kellerman et al 2003 ), and AB12 (Davis et al 1992 )], SV40 TAg transgenic mice [MexTAg, line names TGM299h, TGM304i, TGM270i, and TGM266i (Robinson et al 2006 ), conditional Nf2−/− mice (Jongsma et al 2008 )], and spontaneously immortalized cells obtained after prolonged culturing of primary mouse mesothelial cells (Sherwood et al 2008 ). Here, we established SV40-immortalized mesothelial cells of WT mice and immortalized cells derived from (Nf2+/−) mice; all lines stem from mesothelial cells isolated from mice with C57Bl/6J background.…”
Section: Introductionmentioning
confidence: 99%
“…The most used immortalized human mesothelial cell lines are MeT-5A immortalized with SV40 (Ke et al 1989 ) and LP9 cells immortalized with TERT1, the catalytic component of telomerase (Connell and Rheinwald 1983 ). Immortalized mesothelioma and mesothelial cells of mouse origin include cells isolated from the ascites of asbestos-exposed wild-type C57Bl/6J or BALB/c mice [40, 40L, AE17, AK7 (Cordier Kellerman et al 2003 ), and AB12 (Davis et al 1992 )], SV40 TAg transgenic mice [MexTAg, line names TGM299h, TGM304i, TGM270i, and TGM266i (Robinson et al 2006 ), conditional Nf2−/− mice (Jongsma et al 2008 )], and spontaneously immortalized cells obtained after prolonged culturing of primary mouse mesothelial cells (Sherwood et al 2008 ). Here, we established SV40-immortalized mesothelial cells of WT mice and immortalized cells derived from (Nf2+/−) mice; all lines stem from mesothelial cells isolated from mice with C57Bl/6J background.…”
Section: Introductionmentioning
confidence: 99%
“…Washed cells were resuspended in PBS/5% FCS and analysed on a FACScan analyser (Becton Dickinson, Franklin Lakes, NJ, USA). Cells were also characterized ultrastructurally by transmission electron microscopy (TEM) using standard techniques [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…2009). For example, Sherwood et al. (2008) reported that a spontaneously immortalized mouse cell line displayed characteristics of malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The cells appear to be unsuitable for research on the functions and mechanisms of normal mammary gland cells, because of genomic aberration, cellular heterogeneity and malignancy (Yamasaki et al 2009). For example, Sherwood et al (2008) reported that a spontaneously immortalized mouse cell line displayed characteristics of malignant transformation. Furthermore, like the c-Myc and SV40-immortalized cell lines, these cells underwent modifications of many tumor-related genes, which led to aberrant protein expression (Guerreiro Da Silva et al 2000;Esteban et al 2003;Thibodeaux et al 2009).…”
Section: Introductionmentioning
confidence: 99%